A fast network coding scheme for mobile wireless sensor networks. (February 2017) - Han, Chen; Yang, Yuwang; Han, Xu
In mobile wireless sensor networks, linear network coding has been shown to improve the performance of network throughput and reduce delay. However, the linear dependence of coded packets caused by linear network coding will result in significant instability of the entire network during data transmission. Moreover, current linear network coding schemes do not distinguish between the real-time requirements of different packets. To solve the above problems, a weighted Vandermonde echelon fast coding scheme is proposed based on an analysis of various coding schemes such as random and linear network coding. Weighted Vandermonde echelon fast coding scheme can reduce the dependence problem of the network coding matrix and distinguish between different packet priorities. The accuracy of the proposed weighted Vandermonde echelon fast coding method is investigated through a theoretical analysis and then its outstanding delivery performance is verified through discrete event simulation experiments.